1995
DOI: 10.1038/nm0295-143
|View full text |Cite
|
Sign up to set email alerts
|

Arresting amyloidosis in vivo using small-molecule anionic sulphonates or sulphates: implications for Alzheimer's disease

Abstract: Amyloid is a term for extracellular protein fibril deposits that have characteristic tinctorial and structural properties. Heparan sulphate, or the heparan sulphate proteoglycan perlecan, has been identified in all amyloids and implicated in the earliest stages of inflammation-associated (AA) amyloid induction. Heparan sulphate interacts with the AA amyloid precursor and the beta-peptide of Alzheimer's amyloid, imparting characteristic secondary and tertiary amyloid structural features. These observations sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
218
0
8

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(230 citation statements)
references
References 26 publications
4
218
0
8
Order By: Relevance
“…Tomiyama et al (1996) suggested that Rif binds to Aß by hydrophobic interactions between its lipophilic ansa chain and the hydrophobic region of Aß, thus blocking associations between Aß molecules leading to fAß formation. The anti-amyloidogenic and fibril-destabilizing activity of tetracycline (Tc), small-molecule anionic sulphonates or sulphates, melatonin, ß-sheet breaker peptides (iAß5) and nicotine may also be related to the propensity to bind to the specific sites of Aß (Kisilevsky et al 1995;Soto et al 1996;Pappolla et al 1998;Forloni et al 2001;Zeng et al 2001). Thus, it may be reasonable to consider that NSAIDs could exhibit their anti-amyloidogenic and fibril-destabilizing effects by directly binding to Aßs and/or fAßs.…”
Section: Discussionmentioning
confidence: 99%
“…Tomiyama et al (1996) suggested that Rif binds to Aß by hydrophobic interactions between its lipophilic ansa chain and the hydrophobic region of Aß, thus blocking associations between Aß molecules leading to fAß formation. The anti-amyloidogenic and fibril-destabilizing activity of tetracycline (Tc), small-molecule anionic sulphonates or sulphates, melatonin, ß-sheet breaker peptides (iAß5) and nicotine may also be related to the propensity to bind to the specific sites of Aß (Kisilevsky et al 1995;Soto et al 1996;Pappolla et al 1998;Forloni et al 2001;Zeng et al 2001). Thus, it may be reasonable to consider that NSAIDs could exhibit their anti-amyloidogenic and fibril-destabilizing effects by directly binding to Aßs and/or fAßs.…”
Section: Discussionmentioning
confidence: 99%
“…4). The studies by Snow et al (1) would suggest that complexes formed between A␤-containing peptides and short HS chains do not lead to amyloid deposits, and others have reported that small polysulfated molecules can displace HS glycosaminoglycans or proteoglycans bound to A␤(1-28) affinity columns (29) or disassemble preformed A␤(1-40) fibrils (30). Thus, in addition to degrading the proteoglycan species that would otherwise be found in senile plaques, heparanases may be generating glycosaminoglycan species that act to prevent A␤ aggregation and deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Another set of GAG-based anti-amyloidogenic compounds has been designed according to their ionic properties. Kisilevsky et al [1995] reported that oral and ip administration of poly(vinylsufonate sodium salt), a small-molecule anionic sulfonate, inhibited splenic Ab deposition in a mouse model of inflammation-associated amyloid induction, under both acute and chronic conditions. A different GAG mimetic, 3-amino-1-propanesulfonic acid (Tramiprosate), binds soluble Ab 40 and Ab 42 peptides and maintains them in a random-coil conformation [Gervais et al, 2007].…”
Section: Glycosaminoglycan Mimeticsmentioning
confidence: 99%